Inotropes for Preterm Infants: 50 Years on Are We Any Wiser? - Garvey, Aisling A.; Kooi, Elisabeth M. W.; Dempsey, Eugene M. (Frontiers in Pediatrics, 2018)
For almost half a century, inotropes have been administered to preterm infants with the ultimate goal of increasing their blood pressure. A number of trials, the majority of which focused on dopamine administration, have demonstrated increased blood pressure following inotrope administration in preterm infants and have led to continued use of inotropes in our neonatal units. We have also seen an increase in the number of potential agents available to the clinician. However, we now know that hypotension is a much broader concept than blood pressure alone and our aim should instead be focused on improving end organ perfusion, specifically cerebral perfusion. Only a limited number of studies have incorporated the organ-relevant haemodynamic changes and longer term outcomes when assessing inotropic effects in neonates, the majority of which are observational studies or have a small sample size. In addition, important considerations including the developing/maturing adrenergic receptors, polymorphisms of these receptors, and other differences in the pharmacokinetics and pharmacodynamics of preterm infants, are only recently being recognized. Certainly, there remains huge variation in practice. The lack of well conducted randomised controlled trials addressing these relevant outcomes, along with the difficulty executing such RCTs, leaves us with more questions than answers. This review provides an overview of the various inotropic agents currently being used in the care of preterm infant, with a particular focus on their organ/cerebral haemodynamic effects both during and after transition.